Comparison of semi-active hybrid battery system configurations for electric taxis application. (1st February 2020) - Zhuang, Weichao; Ye, Jianwei; Song, Ziyou; Yin, Guodong; Li, Guangmin
Highlights: Two semi-active hybrid battery systems combining LFP and LTO batteries are proposed. A unified fuzzy-logic energy management strategy is designed to mitigate LFP degradation. Hybrid battery systems were tested in simulated daily electric taxi operation. One system increased battery life more, with 45.4% lifespan improvement. The other achieved 12.49% annual average cost and 39.41% distance-based cost reduction. Abstract: This paper proposes two semi-active configurations for hybrid battery system (HBS) in which L i F e P O 4 (LFP) and L i 4 T i 5 O 12 (LTO) batteries are combined to prolong the life span of LFP batteries used in electric vehicles (EVs). To protect the LFP batteries from frequent peak power demands, the first configuration (HBS #1) uses diodes and switches, while the second (HBS #2) adopts a bidirectional DC/DC convertor to decouple various batteries. To make a fair comparison of the two configurations, their component sizes are firstly determined using brute-force search considering energy capacity and cost. Then, a unified fuzzy-logic energy management strategy was designed and optimized for each configuration to mitigate LFP battery degradation. Simulated implementation of HBSs #1 and 2 in an electric taxi with standard daily operation (driving nearly 400 km per day) and charging patterns revealed that both have longer LFP lifespans (44.4% and 45.4% improvement, respectively), lower annual costs (12.49% and 11.52% reduction, respectively) and reduced distance-based costs (39.41% and 39.18% reduction, respectively) than a single-LFP battery configuration. Although HBS #2 demonstrated more battery life improvement, HBS #1 was found to be cheaper in EV application from the perspectives of total and distance-based cost.